2021
DOI: 10.1111/evo.14371
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the effects of male age and mating history: Contrasting effects of mating history on precopulatory mating behavior and paternity success

Abstract: Many studies ask whether young or older males are better at acquiring mates. Even so, how age affects reproductive success is still poorly understood because male age and mating history are confounded in most studies: older males usually have more mating experience. To what extent does mating history rather than age explain variation in male mating success? And how do mating history and male age determine paternity when there is also postcopulatory sexual selection? Here, we experimentally manipulated the mati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 100 publications
1
6
0
Order By: Relevance
“…This explanation is further supported by our recent experimental studies of the same mosquitofish population where older males achieved significantly higher paternity success than young males (Aich et al. 2021a, b). These results are intriguing, because they support our hypothesis that old male mosquitofish do not show any decline in reproduction success or offspring quality once past mating effort is experimentally controlled.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…This explanation is further supported by our recent experimental studies of the same mosquitofish population where older males achieved significantly higher paternity success than young males (Aich et al. 2021a, b). These results are intriguing, because they support our hypothesis that old male mosquitofish do not show any decline in reproduction success or offspring quality once past mating effort is experimentally controlled.…”
Section: Discussionsupporting
confidence: 65%
“…Third, irrespective of paternal mating history, the sons of older males, to some extent, made more copulation attempts than sons of younger males (p = 0.033). This implies there is evidence of epigenetic heritability of this behavioral trait as we have elsewhere shown that older fathers make more mating attempts (Aich et al 2021a). Overall, our results provide evidence that paternal effects might alter the strength of sexual selection on precopulatory and postcopulatory reproductive traits, establishing an intergenerational link between ageing and sexual selection (Monaghan et al 2020;Vuarin et al 2021).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Contrary to our prediction, males with social learning experience of female receptivity cues did not became choosier or increase their preference towards receptive females in dichotomous choice tests. It may be that that our experimental treatment might have changed the perception of naïve and experienced males in future reproductive opportunities, potentially biasing the investment of naïve males in sexual behaviors that we observed in the first sexual encounter of their pre-treatment test (Fischer et al, 2008, Aich et al, 2021). Furthermore, determining the costs of sexual behaviours are challenging in benign lab environments where food is not a limiting factor.…”
Section: Discussionmentioning
confidence: 99%